An Alternating Projection Framework for Elementwise Masked Nonlinear Matrix Decomposition - Kulathil, Muhammed Noshin Poovan (2025)
A Master of Science thesis in Machine Learning by Muhammed Noshin Poovan Kulathil entitled, “An Alternating Projection Framework for Elementwise Masked Nonlinear Matrix Decomposition”, submitted in November 2025. Thesis advisor is Dr. Mohamed Alhajri. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).